2001
DOI: 10.1021/ma000062+
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Characterization, and Structural Investigations of Poly(ethyl acrylate)-l-polyisobutylene Bicomponent Conetwork

Abstract: A new bicomponent conetwork, poly(ethyl acrylate)-linked-polyisobutylene (PEtA-l-PIB), was synthesized by radical copolymerization of equal amounts of telechelic α,ω-dimethacrylic PIB (MA−PIB−MA, M n/(kg/mol) = 11.2, M w/M n = 1.12, and MA/chain = 2.0) obtained via quasi-living carbocationic polymerization and ethyl acrylate in 10% solution for each component in a common solvent, tetrahydrofuran, followed by extraction and drying. Low amounts of extractables (2.5% in acetone and 4.6% in hexane) and nearly theo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

8
80
0
3

Year Published

2006
2006
2015
2015

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 43 publications
(54 reference statements)
8
80
0
3
Order By: Relevance
“…Polyisobutylenes (PIBs) with different end-groups including chlorine, exoolefin, hydroxyl, and methyl prepared from aliphatic and aromatic initiators were studied by electrospray ionization mass spectrometry (ESI-MS). Independently of the end-groups, presence or absence of aromatic initiator moiety, these PIB derivatives were capable of forming adduct ions with NO 3 -and Cl -ions, thus allowing the direct characterization of these compounds in the negative ion mode of ESI-MS. To obtain [PIB + NO 3 ] -and [PIB + Cl] -adduct ions with appreciable intensities, addition of polar solvents such as acetone, 2-propanol, or ethanol to the dichloromethane solution of PIBs was necessary. Furthermore, increasing both the polarity (by increasing the acetone content) and the ion-source temperature give rise to enhanced intensities for both [PIB + NO 3 ] -and [PIB + Cl] -ions.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Polyisobutylenes (PIBs) with different end-groups including chlorine, exoolefin, hydroxyl, and methyl prepared from aliphatic and aromatic initiators were studied by electrospray ionization mass spectrometry (ESI-MS). Independently of the end-groups, presence or absence of aromatic initiator moiety, these PIB derivatives were capable of forming adduct ions with NO 3 -and Cl -ions, thus allowing the direct characterization of these compounds in the negative ion mode of ESI-MS. To obtain [PIB + NO 3 ] -and [PIB + Cl] -adduct ions with appreciable intensities, addition of polar solvents such as acetone, 2-propanol, or ethanol to the dichloromethane solution of PIBs was necessary. Furthermore, increasing both the polarity (by increasing the acetone content) and the ion-source temperature give rise to enhanced intensities for both [PIB + NO 3 ] -and [PIB + Cl] -ions.…”
mentioning
confidence: 99%
“…Independently of the end-groups, presence or absence of aromatic initiator moiety, these PIB derivatives were capable of forming adduct ions with NO 3 -and Cl -ions, thus allowing the direct characterization of these compounds in the negative ion mode of ESI-MS. To obtain [PIB + NO 3 ] -and [PIB + Cl] -adduct ions with appreciable intensities, addition of polar solvents such as acetone, 2-propanol, or ethanol to the dichloromethane solution of PIBs was necessary. Furthermore, increasing both the polarity (by increasing the acetone content) and the ion-source temperature give rise to enhanced intensities for both [PIB + NO 3 ] -and [PIB + Cl] -ions. Energy-dependent collision induced dissociation studies (CID) revealed that increasing the collision voltages resulted in the shift of the apparent molecular masses to higher ones.…”
mentioning
confidence: 99%
See 3 more Smart Citations